Unknown Archival Materials on Ukrainian-Georgian Literary Contacts: The Way of Borys Ten to Chakhrukhadze - Grytsik, Ludmila; Mchedeladze, Ivane (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2025)
The article discusses yet unknown archival materials which describe the history of the translation of Chakhrukhadze's “Tamariani” (an important monument of old Georgian literature) into Ukrainian as well as the biography of a less-known Ukrainian translator of Georgian literature. The name of the famous Ukrainian translator Borys Ten (Mykola Khomychevkyi 1897–1983) is well known both to the specialists of European and Ancient literature. However, his Ukrainian translations have never been considered by researchers in the context of Ukrainian-Georgian literary relations or fiction translation. The exceptio n was the series of “Poetry of Georgian People” published in two volumes, in which Ukrainian translation of Georgian poetry could be found.